Peran Whistleblowing System dan Big Data Dalam Pendeteksian Fraud Pada Instansi Pemerintah - Permata, Marchelo Boas; Budiwitjaksono, Gideon Setyo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the influence of the whistleblowing system and big data on fraud detection in the public sector. A quantitative approach was employed by distributing questionnaires to 112 auditors of the Audit Board of Indonesia (BPK) in East Java. Data were processed using the SEM-PLS method. The outer model results confirmed the validity and reliability of the research instruments. The structural model test revealed that the whistleblowing system has no significant effect on fraud detection, while big data shows a positive and significant impact. These findings indicate that big data is more effective in supporting audit processes than manual whistleblowing mechanisms. This study contributes theoretically to the literature on fraud detection and provides practical implications for auditors and policymakers in designing technology-based fraud detection systems.